Insect Abundance and Richness in Squash Agroecosystems of Georgia, United States: The Role of Cultivar Selection and Weather Conditions - Sanower Warsi; Yinping Li; George N. Mbata; Alvin M. Simmons (Agronomy, 2025)
This study investigated the abundance and richness of insect pests and beneficial insects on 20 squash cultivars across three seasons in middle Georgia, U.S. Insects were sampled using yellow sticky cards, pan traps and sweep nets. Bemisia tabaci Gennadius (sweet potato whitefly) was prevalent in all seasons, while other key pests showed distinct seasonal peaks. Diaphania hyalinata Linnaeus (melonworm) peaked mid-July in summer 2021 (21 June–1 August), while Thysanoptera species, Acalymma vittatum Fabricius (striped cucumber beetle), and Diabrotica balteata LeConte (banded cucumber beetle) peaked late July-early August. In fall 2021 (4 October–14 November), Epilachna borealis (squash beetle), D. hyalinata, and D. nitidalis Stoll (pickleworm) were more active in early to mid-October, whereas D. undecimpunctata howardi Barber (spotted cucumber beetle) peaked in late November. In fall 2022 (17 October–20 November), D. balteata and D. undecimpunctata howardi peaked mid October to early November, while Anasa tristis DeGeer (squash bug) peaked in mid–late November. Orius insidiosus Say (minute pirate bug) peaked in late summer 2021 and remained stable in fall 2021. Pollinators were most active in mid-fall. Cultivars influenced insect abundance. ‘Saffron’ and ‘Amberpic 8455’ harbored the most O. insidiosus and fewer D. balteata and Thysanoptera species. ‘Golden Goose Hybrid’ had the highest moth numbers. These patterns suggest that cultivar traits influenced pest susceptibility and beneficial arthropods’ activity. Temperature and relative humidity were positively correlated with A. vittatum and E. borealis numbers, but rainfall negatively affected bees. These findings underscore the importance of cultivar selection and weather condition considerations in integrated pest management.